Designing Anthropology Learning Experiences Through Critical Questions Focused on Higher-Order Thinking Skills in the Bloom-Anderson-Krathwohl Taxonomy - Atma Ras; Dimas Ario Sumilih (Pinisi Journal of Social Science, 2026)
This article discusses the design of the anthropology learning experience through critical questions oriented toward Higher-Order Thinking Skills in the Bloom-Anderson-Krathwohl Taxonomy. The main issue examined is the tendency in anthropology education to still emphasize rote learning of concepts, cultural elements, figures, and examples of traditions, thereby failing to fully develop critical and reflective anthropological reasoning. This article employs a conceptual study method with a descriptive-analytical approach. The study examines the relationship between anthropology learning, critical questions based on who, what, where, when, why, and how, and the ability to analyze, evaluate, and create within Higher-Order Thinking Skills. The findings indicate that critical questions can help students understand socio-cultural phenomena through the analysis of actors, values, symbols, spatial contexts, history, causes, processes, and impacts. Critical questions can also be integrated into the formulation of objectives, selection of materials, development of activities, assessment design, and learning reflection. Thus, the design of critical-question-based anthropology learning experiences can strengthen higher-order thinking skills, build anthropological reasoning, and make anthropology learning more analytical, contextual, ethical, and transformative.